The role of a standard family of Ic supernovae in BDHN I, BDHN II, and BDHN III GRBs. Issue 1 (19th February 2023) - Ruffini, Remo; Aimuratov, Yerlan; Becerra, Laura Marcela; Bianco, Carlo Luciano; Cherubini, Christian; Filippi, Simonetta; Li, Liang; Moradi, Rahim; Rastegarnia, Fatemeh; Punsly, Brian; Rueda, Jorge Armando; Sahakyan, Narek; et al.
Abstract: A profound difference has occurred in the analysis of Gamma Ray Bursts (GRBs) initially analyzed in the domain of gamma‐ray astronomy with the Compton Gamma Ray Observatory and the BATSE Detector with the extension to x‐ray astronomy and optical astronomy introduced by Beppo‐SAX and the KEK and VLT optical observatory, followed by the AGILE, Fermi mission, Niels Gehrels SWIFT mission as well as HEHSS and MAGIC observations An authentic "Copernican revolution" has occurred in the transition from the traditional model of GRBs originating in a single star progenitor (collapsar) to GRBs with a binary progenitor composed of a CO core and a companion NS. We have evidence from 24 SN observations related to GRBs that all of them, once analyzed with the general relativistic corrections can be identified with I Bc Sn with a common value of the Luminosity and common time of occurrence of the peak of the optical emission. This can be understood in terms of a precursor composed of a CO core and a binary NS companion. By contrast, the GRBs differ profoundly in their energetics which can be expressed in terms of 3 different classes of BDHNe: BDHN I, BDHN II, and BDHN III, also originating from Precursors composed of a CO core and a Binary companion. It is pointed out how the analysis of these systems has profoundly modified the concept of the BH and the associated fundamental physics necessary for their description since the "introducing of the Black Hole" by Ruffini and Wheeler in 1971. At first, it is illustrated how the most radical change has occurred in the introduction of the effective BH charge, with an electric field only function of the BH dimensionless spin and a background magnetic field Bo. This definitely indicates the abandonment of the Kerr‐Newman solution in favor of the Kerr metric, for energy extraction processes in BH physics. We then enter into the detailed description of the "seven Seals, " the seven Episodes characterizing GRB 190114c, and the associated SN 2019jrj. This is based on the article by Aimuratov et al. (in preparation).